Electrostatic spray cabinet evaluation to verify uniform delivery of chemical and biological solutions to pre-chilled meat animal carcasses - Phebus, Randall C.; Sevart, Nicholas J.; Baumann, Nicholas W.; Phebus, Randall K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Shiga toxin-producing Escherichia coli (STEC) are a group of bacteria that cause an estimated 265,000 illnesses, 3,600 hospitalizations, and 30 deaths annually in the United States. STEC are frequently associated with raw or undercooked meat products, prompting the beef industry to develop and apply various antimicrobial intervention technologies during processing operations. The application of chemical antimicrobials to carcasses and fabricated cuts using an electrostatic spray (ESS) system (Figure 1) offers several potential advantages for controlling disease-causing pathogens, including enhanced chemical deposition (coverage) profiles, reduced overspray wastage of foodgrade antimicrobials, and reduced water requirements. The objectives of this study were to (1) calibrate an ESS carcass cabinet installed at the Kansas State University Biosecurity Research Institute, (2) test the chemical deposition profile of the ESS cabinet onto a meat carcass using fluorescent dye, and (3) determine if the ESS could be used to uniformly apply a biological inoculum to a carcass to support pathogen-inoculated validation studies of different chemical intervention technologies to support the needs of the beef processing industry.
Keywords: Beef; Electrostatic spray; Shiga toxin-producing E. coli